Side effects of COVID-19 vaccination in Pakistani population: A cross sectional study - Ain, Quratul; Khan, Madeeha; Afrah, Aleena; Akmal, Zainab; Javed, Sadia; Nawaz, Amjad; Khan, Mohammad Iqbal; Sadiq, Fouzia (Bangladesh Journal of Medical Science, 2024)
Objectives Data from clinical trials around the world show that the COVID-19 vaccines are effective in terms of reducing hospitalization need for respiratory support and deaths. However, to assess common or uncommon adverse events of the COVID-19 vaccines, data from real world experiences need to be evaluated to resolve the speculations associated with the vaccines. Materials and Methods A questionnaire based on demographic details, vaccination details, side effects experienced, the duration of side effects and COVID-19 status was administered to study participants during this cross-sectional study. Results and Discussion A total of 1162 responses were collected from fully vaccinated individuals, where Sinovac was the highly administered vaccine (40%). Most of the vaccinated participants (94%) did not contract SARS-CoV-2 infection following vaccination; however, the rate of hospitalization (4.2%) and development of extreme complications (1.4%) was lower in those who contracted the disease after vaccination compared to those who contracted COVID-19 before being fully vaccinated (7.1%). The most frequent side effects of vaccination reported were moderate pain at the site of injection administration, muscle pain, headache, fever, fatigue, swelling, redness or pain at the site of injection, nausea and joint pain. Only 2% of the participants encountered extreme daily routine difficulties while most of the side effects resolved within one week (30%). Conclusion: The present study reports mild post vaccination side effects and low incidence of SARS-CoV-2 following COVID-19 vaccination. These results may help in improving the public perception and confidence towards COVID-19 vaccination in the Pakistani population. Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 355-367